Determination of Industrial Enterprise Contract Demand Being Part of Maximum Power System Load - V. N. Radkevich; О. А. Trifonova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a regime and economic essence of the problem pertaining to determination of the customer contract demand for industrial consumers of electric power with connected load of Sпp > 250 kV×A. A method for determination of the electric power customer half-hour maximum demand is proposed in the paper. The method is based on the calculation of daily average active load and utilization factor with due account of the occurrence probability of a calculated maximum load value.